Copper-based catalyst as well as preparation method and application thereof

The copper-based catalyst prepared by hydrogen reduction combined with photoreduction method solves the problems of low activity and easy sintering of existing copper-based catalysts, achieves high carbon dioxide conversion rate and high carbon monoxide selectivity, and has high industrial application prospects.

CN119588352AActive Publication Date: 2025-03-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411772365.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing copper-based catalysts have low catalytic activity and are easy to sinter in the reverse water gas transformation reaction, making it difficult to achieve high carbon dioxide conversion and high carbon monoxide selectivity.

Method used

Copper-based catalysts were prepared by hydrogen reduction combined with photoreduction. The nanotitanium dioxide support was treated at high temperature, surface defects and oxygen vacancies were introduced, and copper metal was deposited under xenon light irradiation to achieve high dispersion of the copper active center.

Benefits of technology

The catalytic activity and high temperature stability of the catalyst are improved, the formation of by-products methane and methanol is significantly inhibited, the selectivity of carbon monoxide is improved, and the industrial application prospects are high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588352A_ABST
    Figure CN119588352A_ABST
Patent Text Reader

Abstract

The invention provides a copper-based catalyst as well as a preparation method and application thereof, and relates to the technical field of preparation of reverse water gas shift reaction catalysts. High-temperature hydrogen reduction is combined with photo-reduction treatment, rich surface defects and oxygen vacancies are introduced to the surface of the carrier, copper metal is further photo-deposited, a copper active center is anchored to the surface of the carrier under the strong interaction of the rich surface defects and the metal carrier, meanwhile, aggregation of the copper active center is inhibited, and the activity of the carrier is improved. High dispersion of a copper active center is realized, so that the catalytic activity and high-temperature stability of the catalyst are improved, and the catalyst has the characteristics of high carbon dioxide conversion rate, high carbon monoxide selectivity and stability in a reverse water gas shift reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of reverse water-gas shift reaction catalysts, and in particular to a copper-based catalyst and a preparation method and application thereof. Background Art

[0002] With the rapid increase in carbon dioxide emissions, the greenhouse effect has intensified the impact on the global ecosystem, which has attracted global attention. Therefore, it is imperative to solve global environmental problems by utilizing carbon dioxide as a resource and reducing the concentration of carbon dioxide in the atmosphere. The reverse water gas shift (RWGS) reaction is one of the most valuable ways to utilize carbon dioxide as a resource by catalytically converting carbon dioxide into more valuable carbon monoxide. In the modern chemical industry, carbon monoxide and hydrogen can be further synthesized into important, high-value-added chemical products such as olefins, alcohols, formaldehyde, etc. through the Fischer-Tropsch reaction.

[0003] At present, the catalysts for the reverse water gas shift reaction mainly include precious metal-based catalysts and non-precious metal-based catalysts. Among them, precious metal-based catalysts are mainly Pt, Au, Rh and Pd, etc. Although they have high catalytic activity, they are expensive and difficult to achieve industrial application. Therefore, the development of non-precious metal catalyst systems with high catalytic activity has been widely studied. Copper-based catalysts have received special attention as substitutes for precious metal catalysts in RWGS reactions due to their low cost and high carbon monoxide selectivity. However, copper-based catalysts still have problems such as low catalytic activity and easy sintering. Chinese patent CN 107497439A uses a silica sol method to prepare a copper-cerium catalyst with a mesoporous structure, so that the catalyst has good thermal stability and carbon monoxide selectivity, but the activity of the catalyst needs to be further improved. Chinese patent CN103230799A discloses a Cu-Zn-based catalyst for the reverse water gas shift reaction, which has high reaction activity at low temperatures, but low carbon monoxide selectivity, and other oxygen-containing compounds are present in the product.

[0004] In summary, the development of copper-based reverse water-gas shift catalysts with both high activity and good stability remains challenging and of practical significance. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a catalyst for reverse water-gas shift reaction and a preparation method thereof. The copper active sites in the catalyst prepared by the present invention are highly dispersed, and it has the characteristics of high carbon dioxide conversion rate and high carbon monoxide selectivity in the reverse water-gas shift reaction.

[0006] One of the purposes of the present invention is to provide a method for preparing a copper-based catalyst.

[0007] A second object of the present invention is to provide a copper-based catalyst prepared by the preparation method.

[0008] The third object of the present invention is to provide an application of the copper-based catalyst.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] In a first aspect, the present invention provides a method for preparing a copper-based catalyst, comprising the following steps:

[0011] S1, placing nano titanium dioxide in a tube furnace and subjecting it to high temperature treatment under a hydrogen atmosphere;

[0012] S2, dissolving the nano titanium dioxide after high temperature treatment in a methanol aqueous solution, and stirring evenly under the condition of introducing nitrogen to obtain a nano titanium dioxide solution;

[0013] S3, turning on the xenon lamp light source to expose the nano titanium dioxide solution to the xenon lamp light;

[0014] S4, injecting the copper salt aqueous solution into the nano titanium dioxide solution, and continuing to stir under the irradiation of xenon light to obtain a mixed solution, wherein the content of copper ions is 2wt%-8wt% based on the mass of the nano titanium dioxide;

[0015] S5. Washing and drying the obtained mixed solution to obtain a copper-based catalyst.

[0016] The active center of the copper-based catalyst prepared by the hydrogen reduction combined with photoreduction method is highly dispersed copper metal.

[0017] Step S1:

[0018] In step S1, the nano titanium dioxide is commercial nano titanium dioxide, preferably with an average particle size of 20 nm to 30 nm, and a rutile phase structure.

[0019] In some embodiments, in step S1, the flow rate of hydrogen is 20 mL / min to 60 mL / min, the high temperature treatment temperature is 200° C. to 500° C., the heating rate is 2 to 5° C. / min, and the treatment time is 1 h to 5 h.

[0020] Step S2:

[0021] In some embodiments, in step S2, the volume of the methanol aqueous solution is 50 mL to 200 mL for every 500 mg of nano-titanium dioxide, and the volume proportion of methanol in the methanol aqueous solution is 5% to 50%;

[0022] In some embodiments, in step S2, the flow rate of nitrogen is 20 mL / min to 60 mL / min, the stirring speed is 300 r / min to 1000 r / min, and the stirring time is 0.5 h to 3 h.

[0023] Step S3:

[0024] In some embodiments, in step S3, the power of the xenon lamp light source is 100W to 800W, and the irradiation time is 0.1h to 2h.

[0025] Step S4:

[0026] In some embodiments, in step S4, the copper salt is one or more of copper nitrate hexahydrate, copper sulfate pentahydrate, and copper chloride;

[0027] In some embodiments, in step S4, the volume of the copper salt aqueous solution is 1 mL to 5 mL, and the concentration is 0.1 to 1 mol / L for every 500 mg of nano-titanium dioxide.

[0028] In some embodiments, in step S4, the stirring time is 0.1 h to 2 h.

[0029] Step S5:

[0030] In some embodiments, in step S5, centrifugal washing is performed with ethanol and water respectively, and the number of centrifugal washings is 1 to 5 times for each of ethanol and water;

[0031] In some embodiments, in step S3, the drying operation process is placing in a vacuum drying oven and drying overnight at a drying temperature of 50 to 80°C.

[0032] In a second aspect, the present invention provides a copper-based catalyst prepared by the above-mentioned preparation method, wherein the copper-based catalyst comprises a nano-TiO2 carrier, and highly dispersed copper nanoparticles supported on the nano-TiO2 carrier; the size of the copper nanoparticles is 3nm to 5nm;

[0033] The copper loading is 2 wt% to 8 wt% based on the mass of the TiO2 support.

[0034] In some embodiments, the average particle size of nano-titanium dioxide is 20 nm to 30 nm, and the physical phase is a rutile phase structure.

[0035] In a third aspect, the present invention provides an application of the above copper-based catalyst in a reverse water-gas shift reaction.

[0036] Preferably, the reaction is carried out in a fixed bed reactor;

[0037] The catalyst is tableted, crushed, and sieved into particles of 20-40 mesh and loaded into a fixed bed reactor.

[0038] The reaction conditions are as follows: reaction temperature is 400-500°C, reaction pressure is 0.1-0.5MPa, total space velocity of raw gas is 3000-8000mL / g / h, and the gas used is a mixture of CO2 and H2, wherein the volume ratio of CO2 to H2 is 1:1-1:4.

[0039] Preferably, the copper-based catalyst is subjected to hydrogen pre-reduction treatment before use, and the reduction conditions are: hydrogen space velocity of 3000mL / g / h to 10000mL / g / h, reduction temperature of 200°C to 400°C, and reduction time of 0.5h to 5h.

[0040] Technical effects:

[0041] (1) The preparation method of the present invention has a simple operation process and low cost;

[0042] (2) The preparation method of the present invention adopts high-temperature hydrogen reduction combined with photoreduction treatment to introduce abundant surface defects and oxygen vacancies to the surface of the carrier, and further photodeposit copper metal to anchor the copper active center to the surface of the carrier under the strong interaction between abundant surface defects and metal carrier, and at the same time inhibit the aggregation of copper active centers, thereby achieving high dispersion of copper active centers, thereby improving the catalytic activity and high temperature stability of the catalyst;

[0043] (3) The catalyst prepared by the present invention exhibits excellent catalytic activity in the reverse water gas reaction test, significantly inhibits the formation of by-products methane and methanol, improves the selectivity of carbon monoxide, and has a high industrial application prospect.

[0044] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a high-resolution transmission electron microscopy image of the catalyst prepared in Example 2.

[0046] Figure 2 The following are the performance test results of the catalysts prepared in the examples and comparative examples. DETAILED DESCRIPTION

[0047] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.

[0048] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.

[0049] Example 1

[0050] (1) Place 500 mg of nano-titanium dioxide (P25) in a tube furnace, introduce 30 mL / min of high-purity hydrogen, and heat to 400 °C at a heating rate of 2 °C / min, and maintain for 3 h;

[0051] (2) The treated titanium dioxide was dissolved in 100 mL of 20% methanol aqueous solution, 30 mL / min of nitrogen was introduced to exclude air, and then the stirring speed was maintained at 500 r / min for 2 h;

[0052] (3) Turn on the xenon lamp light source so that the solution is exposed to the xenon lamp light for 0.5 h, where the power of the xenon lamp light source is 300 W;

[0053] (4) 46.3 mg of copper nitrate hexahydrate was dissolved in 1 mL of deionized water, and then injected into the above solution. The mixture was stirred for 1 h under the irradiation of a xenon lamp, wherein the loading amount of copper relative to the nano-titanium dioxide carrier was 2 wt %;

[0054] (5) The solution was washed three times by centrifugation with ethanol and water respectively, and then placed in a vacuum drying oven at 60° C. to dry overnight. The catalyst was collected for testing.

[0055] The catalyst was tableted, crushed, sieved into 20-40 mesh particles and loaded into a fixed bed reactor. The catalyst was pre-reduced with hydrogen before the reaction test. The pretreatment conditions were: hydrogen space velocity 6000mL / g / h, reduction temperature 300℃, and reduction time 2h. After the temperature dropped to room temperature, the reaction gas was introduced. The reaction conditions were: reaction temperature 480℃, reaction pressure 0.1MPa, total feed gas space velocity 4000mL / g / h, and the volume ratio of carbon dioxide and hydrogen in the feed gas was 1:2. The catalytic reaction performance test results are shown in Figure 2 .

[0056] Example 2

[0057] (1) Place 500 mg of nano-titanium dioxide (P25) in a tube furnace, introduce 30 mL / min of high-purity hydrogen, and heat to 400 °C at a heating rate of 2 °C / min, and maintain for 3 h;

[0058] (2) The treated titanium dioxide was dissolved in 100 mL of 20% methanol aqueous solution, 30 mL / min of nitrogen was introduced to exclude air, and then the stirring speed was maintained at 500 r / min for 2 h;

[0059] (3) Turn on the xenon lamp light source so that the solution is exposed to the xenon lamp light for 0.5 h, where the power of the xenon lamp light source is 300 W;

[0060] (4) 92.6 mg of copper nitrate hexahydrate was dissolved in 1 mL of deionized water, and then injected into the above solution. Stirring was continued for 1 h under the irradiation of xenon light, wherein the copper loading was 4 wt%;

[0061] (5) The solution was washed three times by centrifugation with ethanol and water respectively, and then placed in a vacuum drying oven at 60° C. to dry overnight. The catalyst was collected for testing.

[0062] Its transmission electron microscopy image is as follows Figure 1 As shown, from Figure 1 It can be seen that the dispersion of copper in the catalyst is high, with a size of about 3nm to 5nm.

[0063] The catalyst was tableted, crushed, sieved into 20-40 mesh particles and loaded into a fixed bed reactor. The catalyst was pre-reduced with hydrogen before the reaction test. The pretreatment conditions were: hydrogen space velocity 6000mL / g / h, reduction temperature 300℃, and reduction time 2h. After the temperature dropped to room temperature, the reaction gas was introduced. The reaction conditions were: reaction temperature 480℃, reaction pressure 0.1MPa, total feed gas space velocity 4000mL / g / h, and the volume ratio of carbon dioxide and hydrogen in the feed gas was 1:2. The catalytic reaction performance test results are shown in Figure 2 .

[0064] Example 3

[0065] (1) Place 500 mg of nano-titanium dioxide (P25) in a tube furnace, introduce 30 mL / min of high-purity hydrogen, and heat to 400 °C at a heating rate of 2 °C / min, and maintain for 3 h;

[0066] (2) The treated titanium dioxide was dissolved in 100 mL of 20% methanol aqueous solution, 30 mL / min of nitrogen was introduced to exclude air, and then the stirring speed was maintained at 500 r / min for 2 h;

[0067] (3) Turn on the xenon lamp light source so that the solution is exposed to the xenon lamp light for 0.5 h, where the power of the xenon lamp light source is 300 W;

[0068] (4) 138.9 mg of copper nitrate hexahydrate was dissolved in 1 mL of deionized water, and then injected into the above solution. Stirring was continued for 1 h under the irradiation of xenon light, wherein the copper loading was 6 wt%;

[0069] (5) The solution was washed three times by centrifugation with ethanol and water respectively, and then placed in a vacuum drying oven at 60° C. to dry overnight. The catalyst was collected for testing.

[0070] The catalyst was tableted, crushed, sieved into 20-40 mesh particles and loaded into a fixed bed reactor. The catalyst was pre-reduced with hydrogen before the reaction test. The pretreatment conditions were: hydrogen space velocity 6000mL / g / h, reduction temperature 300℃, and reduction time 2h. After the temperature dropped to room temperature, the reaction gas was introduced. The reaction conditions were: reaction temperature 480℃, reaction pressure 0.1MPa, total feed gas space velocity 4000mL / g / h, and the volume ratio of carbon dioxide and hydrogen in the feed gas was 1:2. The catalytic reaction performance test results are shown in Figure 2 .

[0071] Example 4

[0072] (1) Place 500 mg of nano-titanium dioxide (P25) in a tube furnace, introduce 30 mL / min of high-purity hydrogen, and heat to 400 °C at a heating rate of 2 °C / min, and maintain for 3 h;

[0073] (2) The treated titanium dioxide was dissolved in 100 mL of 20% methanol aqueous solution, 30 mL / min of nitrogen was introduced to exclude air, and then the stirring speed was maintained at 500 r / min for 2 h;

[0074] (3) Turn on the xenon lamp light source so that the solution is exposed to the xenon lamp light for 10 min, where the power of the xenon lamp light source is 300 W;

[0075] (4) 92.6 mg of copper nitrate hexahydrate was dissolved in 1 mL of deionized water, and then injected into the above solution. Stirring was continued for 1 h under the irradiation of xenon light, wherein the copper loading was 4 wt%;

[0076] (5) The solution was washed three times by centrifugation with ethanol and water respectively, and then placed in a vacuum drying oven at 60° C. to dry overnight. The catalyst was collected for testing.

[0077] The catalyst was tableted, crushed, sieved into 20-40 mesh particles and loaded into a fixed bed reactor. The catalyst was pre-reduced with hydrogen before the reaction test. The pretreatment conditions were: hydrogen space velocity 6000mL / g / h, reduction temperature 300℃, and reduction time 2h. After the temperature dropped to room temperature, the reaction gas was introduced. The reaction conditions were: reaction temperature 480℃, reaction pressure 0.1MPa, total feed gas space velocity 4000mL / g / h, and the volume ratio of carbon dioxide and hydrogen in the feed gas was 1:2. The catalytic reaction performance test results are shown in Figure 2 .

[0078] Comparative Example 1: No Xenon Lamp Irradiation Pretreatment

[0079] (1) Place 500 mg of nano-titanium dioxide (P25) in a tube furnace, introduce 30 mL / min of high-purity hydrogen, and heat to 400 °C at a heating rate of 2 °C / min, and maintain for 3 h;

[0080] (2) The treated titanium dioxide was dissolved in 100 mL of 20% methanol aqueous solution, 30 mL / min of nitrogen was introduced to exclude air, and then the stirring speed was maintained at 500 r / min for 2 h;

[0081] (3) Turn on the xenon lamp light source, dissolve 92.6 mg of copper nitrate hexahydrate in 1 mL of deionized water, and then inject it into the above solution. Continue stirring for 1 hour under the irradiation of the xenon lamp, wherein the power of the xenon lamp light source is 300 W and the copper loading is 4 wt%;

[0082] (4) The solution was washed three times by centrifugation with ethanol and water respectively, and then placed in a vacuum drying oven at 60° C. to dry overnight. The catalyst was collected for testing.

[0083] The catalyst was tableted, crushed, sieved into 20-40 mesh particles and loaded into a fixed bed reactor. The catalyst was pre-reduced with hydrogen before the reaction test. The pretreatment conditions were: hydrogen space velocity 6000mL / g / h, reduction temperature 300℃, and reduction time 2h. After the temperature dropped to room temperature, the reaction gas was introduced. The reaction conditions were: reaction temperature 480℃, reaction pressure 0.1MPa, total feed gas space velocity 4000mL / g / h, and the volume ratio of carbon dioxide and hydrogen in the feed gas was 1:2. The catalytic reaction performance test results are shown in Figure 2 .

[0084] Comparative Example 2: No Hydrogen Reduction Pretreatment

[0085] (1) Dissolve 500 mg of nano-titanium dioxide (P25) in 100 mL of 20% methanol aqueous solution, introduce 30 mL / min of nitrogen to exclude air, and then maintain the stirring speed at 500 r / min for 2 h;

[0086] (2) Turn on the xenon light source to expose the solution to the xenon light for 0.5 h, wherein the power of the xenon light source is 300 W; 92.6 mg of copper nitrate hexahydrate is dissolved in 1 mL of deionized water, and then injected into the above solution, and continue stirring for 1 h under the irradiation of the xenon light, wherein the copper loading is 4 wt%;

[0087] (3) The solution was washed three times by centrifugation with ethanol and water respectively, and then placed in a vacuum drying oven at 60° C. to dry overnight. The catalyst was collected for testing.

[0088] The catalyst was tableted, crushed, sieved into 20-40 mesh particles and loaded into a fixed bed reactor. The catalyst was pre-reduced with hydrogen before the reaction test. The pretreatment conditions were: hydrogen space velocity 6000mL / g / h, reduction temperature 300℃, and reduction time 2h. After the temperature dropped to room temperature, the reaction gas was introduced. The reaction conditions were: reaction temperature 480℃, reaction pressure 0.1MPa, total feed gas space velocity 4000mL / g / h, and the volume ratio of carbon dioxide and hydrogen in the feed gas was 1:2. The catalytic reaction performance test results are shown in Figure 2 .

[0089] The calculation process of CO2 conversion rate and selectivity of each component is as follows:

[0090]

[0091] Among them, [CO2] inlet and [CO2] outlet Represent the molar concentration of CO2 in the raw gas and tail gas respectively.

[0092]

[0093] Among them, [CO], [C i H x ] represent the molar concentrations of CO and hydrocarbons, respectively.

[0094] from Figure 2 It can be seen that compared with the examples, the catalyst prepared by hydrogen reduction combined with photoreduction treatment of the carrier exhibits higher catalytic activity and carbon monoxide selectivity. This shows that the preparation method of the present invention can effectively improve the dispersion of copper active sites, inhibit agglomeration, and thus significantly enhance the activation ability of the catalyst for carbon dioxide, and avoid excessive hydrogenation reaction of the generated carbon monoxide, so when the reaction temperature is 480°C, the selectivity of carbon monoxide is as high as 95%.

[0095] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.

Claims

1. A method for preparing a copper-based catalyst, characterized in that: The following steps are involved: S1, placing nano titanium dioxide in a tube furnace and subjecting it to high temperature treatment under a hydrogen atmosphere; S2, dissolving the nano titanium dioxide after high temperature treatment in a methanol aqueous solution, and stirring evenly under the condition of introducing nitrogen to obtain a nano titanium dioxide solution; S3, turning on the xenon lamp light source to expose the nano titanium dioxide solution to the xenon lamp light; S4, injecting the copper salt aqueous solution into the nano titanium dioxide solution, and continuing to stir under the irradiation of xenon light to obtain a mixed solution, wherein the content of copper ions is 2wt%-8wt% based on the mass of the nano titanium dioxide; S5. Washing and drying the obtained mixed solution to obtain a copper-based catalyst.

2. The preparation method according to claim 1, characterized in that: In step S1, the flow rate of hydrogen is 20 mL / min to 60 mL / min, the high temperature treatment temperature is 200° C. to 500° C., the heating rate is 2 to 5° C. / min, and the treatment time is 1 h to 5 h.

3. The preparation method according to claim 1, characterized in that: In step S2, the volume of the methanol aqueous solution is 50 mL to 200 mL for every 500 mg of nano-titanium dioxide, and the volume proportion of methanol in the methanol aqueous solution is 5% to 50%.

4. The preparation method according to claim 1, characterized in that: In step S2, the flow rate of nitrogen is 20 mL / min to 60 mL / min, the stirring speed is 300 r / min to 1000 r / min, and the stirring time is 0.5 h to 3 h.

5. The preparation method according to claim 1, characterized in that: In step S3, the power of the xenon lamp light source is 100W to 800W, and the irradiation time is 0.1h to 2h.

6. The preparation method according to claim 1, characterized in that: In step S4, the copper salt is one or more of copper nitrate hexahydrate, copper sulfate pentahydrate, and copper chloride; In step S4, for every 500 mg of nano-titanium dioxide, the volume of the copper salt aqueous solution is 1 mL to 5 mL, and the concentration is 0.1 to 1 mol / L.

7. The preparation method according to claim 1, characterized in that: In step S4, the stirring time is 0.1 h to 2 h.

8. A copper-based catalyst, characterized in that The copper-based catalyst is prepared by the preparation method described in any one of claims 1 to 7, comprising a nano-TiO2 carrier and highly dispersed copper nanoparticles loaded on the nano-TiO2 carrier; the size of the copper nanoparticles is 3nm to 5nm; based on the mass of the TiO2 carrier, the copper loading is 2wt% to 8wt%.

9. Use of the copper-based catalyst according to claim 8 in a reverse water gas shift reaction.

10. The use according to claim 9, characterized in that: The reaction is carried out in a fixed bed reactor; the reaction conditions are: reaction temperature is 400-500°C, reaction pressure is 0.1-0.5MPa, total space velocity of feed gas is 3000-8000mL / g / h, and the gas used is a mixture of CO2 and H2, wherein the volume ratio of CO2 to H2 is 1:1-1:4; Preferably, the copper-based catalyst is subjected to hydrogen pre-reduction treatment before use, and the reduction conditions are: hydrogen space velocity of 3000mL / g / h to 10000mL / g / h, reduction temperature of 200°C to 400°C, and reduction time of 0.5h to 5h.

Citation Information

Patent Citations

  • Cu-Zn-based catalyst used in reverse water gas shift reaction, and preparation method and application thereof

    CN103230799A

  • Copper-based catalyst for reverse water-gas shift reaction and preparation method therefor

    CN107497439A

  • Methods for conversion of CO2 into syngas

    CN107530683A

  • Atom-scale dispersion copper CO2 conversion cocatalyst and preparation method and application thereof

    CN109939679A

  • Preparation method of black TiO2 nanosheet photocatalyst

    CN111821966A